2014
DOI: 10.1021/am5066859
|View full text |Cite
|
Sign up to set email alerts
|

Porous Polyurea Network Showing Aggregation Induced White Light Emission, Applications as Biosensor and Scaffold for Drug Delivery

Abstract: We have designed a urea functionalized novel nanoporous material, POP-PU, which showsaggregation induced white light emission in the presence of suitable polar solvents. This nanomaterial has been explored as a pseudowhite light emitter where the polymeric luminogen moiety can interact with the suitable polar solvent, leading to charge transfer. Thus, solvent assisted rotational freezing of nonrigid polymeric nanoparticles gives radiative emission and the whole solution emits white light with color temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…Solid-state light emitting materials, especially white light emitting materials, are of particular interest in recent years due to their potential applications in display and lighting. [138][139][140] Li and coworkers designed a ligand H 4 tcbpe 4′,4′′′,4′′′′′,4′′′′′′-(ethene-1,1,2,2-tetrayl)tetrakis ([1,10-biphenyl]-4-carboxylic acid), emitting near 540 nm and coordinated with Zn ion to form LMOFs with high internal and external quantum yields (Figure 13a). [141] The obtained crystals show high surface area and emit near-yellow fluorescence.…”
Section: Solid-state Light Emittingmentioning
confidence: 99%
“…Solid-state light emitting materials, especially white light emitting materials, are of particular interest in recent years due to their potential applications in display and lighting. [138][139][140] Li and coworkers designed a ligand H 4 tcbpe 4′,4′′′,4′′′′′,4′′′′′′-(ethene-1,1,2,2-tetrayl)tetrakis ([1,10-biphenyl]-4-carboxylic acid), emitting near 540 nm and coordinated with Zn ion to form LMOFs with high internal and external quantum yields (Figure 13a). [141] The obtained crystals show high surface area and emit near-yellow fluorescence.…”
Section: Solid-state Light Emittingmentioning
confidence: 99%
“…This isotherm indicated a steady increase in N 2 uptake from low to high P/P 0 together with a large hysteresis loop. Thus, this N 2 sorption analysis suggested the presence of a wide range of micropores to mesopores in the material . At low pressure (0.07–0.2 P/P 0 ) region large N 2 uptake is observed, suggesting the presence of micropores.…”
Section: Resultsmentioning
confidence: 63%
“…Thus, this N 2 sorption analysis suggested the presence of a wide range of micropores to mesopores in the material. [37] At low pressure (0.07-0.2 P/P 0 ) region large N 2 uptake is observed, suggesting the presence of micropores. On the other hand at high pressure region (P/P 0 = 0.55-0.99) also there is a steady increase in N 2 uptake together with a desorption hysteresis.…”
Section: Resultsmentioning
confidence: 94%
“…[1][2][3][4][5][6] To date, some studies have reported the design of drug-delivery systems based on the nanoporous materials for loading therapeutic molecules, such as chemical drugs, peptides, and proteins. 7,8 As an effective vector-delivering therapeutic molecules, the nanoporous materials with the pore size of a few nanometers have high capacity to encapsulate large amounts of drugs/biomolecules. 9 Recently, the use of nanoporous materials for bone repair has been proposed, and the tunable pore size, large surface area, and high pore volume might allow them to load osteogenic agents and promote new bone regeneration.…”
Section: Introductionmentioning
confidence: 99%